2018
DOI: 10.1038/s41598-018-19591-9
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast genomic resources for phylogeny and DNA barcoding: a case study on Fritillaria

Abstract: The genus Fritillaria comprises approximately 130 perennial herbaceous species. In the Pharmacopoeia of the People’s Republic of China, the bulbs of 11 Fritillaria species are used in Chinese herbal medicines. However, the traditional methods of morphological classification cannot accurately identify closely related species of Fritillaria. Previous studies have attempted to identify these species with universal molecular markers, but insufficient phylogenetic signal was available. In this study, the complete c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
104
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 57 publications
17
104
2
Order By: Relevance
“…Our results revealed that the whole plastome sequences of 11 newly sequenced Fritillaria species were conserved not only in genome size, but also in gene content, structure, and order (Figure 1), which was consistent with previously published Fritillaria plastomes studies [23][24][25]. Nevertheless, some CDS genes exhibited high variations, mainly in some pseudogenes, for example ψycf15, ψycf68, and ψinfA, which were also reported in other angiosperm plastid genomes [7,9,26,27].…”
Section: Comparison Of Fritillaria Plastomes and Phylogenetically Infsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results revealed that the whole plastome sequences of 11 newly sequenced Fritillaria species were conserved not only in genome size, but also in gene content, structure, and order (Figure 1), which was consistent with previously published Fritillaria plastomes studies [23][24][25]. Nevertheless, some CDS genes exhibited high variations, mainly in some pseudogenes, for example ψycf15, ψycf68, and ψinfA, which were also reported in other angiosperm plastid genomes [7,9,26,27].…”
Section: Comparison Of Fritillaria Plastomes and Phylogenetically Infsupporting
confidence: 90%
“…Therefore, the relationships between the New World and the Old World clades of Fritillaria and Lilium still remain unsolved. In comparison with previous studies [24,25], our results detected further phylogenetic relationships between Fritillaria and Lilium with more plastomes data, and the subgenus Fritillaria was confirmed polyphyletic, which has a high resolution than previous studies ( Figure 5) [16,17]. Our results also proved that the plastome data are of great advantages in phylogenetic analyses, although more extensive plastid genomic sampling was needed for further resolution of Fritillaria and Lilium.…”
Section: Phylogenetic Relationships and Implicationssupporting
confidence: 71%
See 1 more Smart Citation
“…Our results revealed that the whole plastome sequences newly obtained herein for 11 Fritillaria species only slightly vary in size (151,652bp-152,434bp) (Table1), and also largely similar in overall gene content, structure and order (Fig.1). The genome size in our study is accord with previously sequenced plastid genomes of Fritillaria [23][24][25]. Nonetheless, we have been able to document that the CDS genes vary in the plastomes of these eleven species, mainly there are particular (pseudo) genes: ψycf15, ψycf68 and ψinfA in some species.…”
Section: Comparison Of Fritillaria Plastomes and Phylogenetically Infsupporting
confidence: 86%
“…Thus, the relationship between the New World and the Old world clades of Fritillaria and Lilium still remains unsolved. But our results provide further evidence for relationships between the two clades of Fritillaria and Lilium from phylogenomic analyses based on the most complete plastid genomes sampling by far compared with those of the earlier study by Bi et al [24] and Li et al [25]. More extensive plastid genomic sampling should be needed for further resolution.…”
Section: Phylogenetic Relationships and Implicationssupporting
confidence: 73%